Amino antioxidants: A review of their environmental behavior, human exposure, and aquatic toxicity. (March 2023) - Jin, Ruihe; Venier, Marta; Chen, Qiqing; Yang, Jing; Liu, Min; Wu, Yan
Abstract: Amino antioxidants (AAOs), a suite of emerging organic contaminants, have been widely used in numerous industrial and commercial products to inhibit oxidation and corrosion. Recently, their environmental ubiquity, health risks, bioaccumulative and toxic potential have led to mounting public concern. This review summarizes the current state of knowledge on the production and usage, environmental occurrence, bioavailability, human exposure, and aquatic toxicity of representative AAOs, and provides suggestions for future research directions. Previous studies have revealed widespread distribution of many AAOs in various environmental matrixes, including air, water, sediment, dust, and biota. In addition to parent compounds, their degradation products, such as 2-anilino-5-(1, 3-dimethylbutylamino)-1, 4-benzoquinone (6PPD-Q) and 4-nitrodiphenylamine (4-NO2 -DPA), have also been detected at high levels in multiple compartments. Dust ingestion and air inhalation are the two most well-investigated routes for human exposure to AAOs and their transformation products, while studies on other pathways (e.g., skin contact and dietary intake) still remain extremely limited. Moreover, AAO burdens in human tissue have been poorly documented. Toxicological data have shown that a few AAOs may cause teratogenic, developmental, reproductive, endocrinic, neuronic, and genetic toxicity to aquatic organisms, and the toxic capacities of degradation products differ from their precursors. Future studies should focus on elucidating AAO exposure for humans and associated health risks. Additionally, more attention should be given to AAO transformation products (particularly those quinoid derivatives possessing substantial affinity with DNA) and to the effects of complex mixtures of these chemicals. Graphical abstract: Image 1 Highlights: Environmental profiles of amino antioxidants (AAOs) are comprehensively compiled. Both wildlife and humans are experiencing appreciable exposure to AAOs. Research concerning aquatic toxicity of AAOs remains relatively lagged. Studies should be extended to transformation products and less-studied AAOs.